Use of probiotics to reduce faecal shedding of Shiga toxin-producing Escherichia coli in sheep - Rigobelo, Everlon Cid [UNESP]; Karapetkov, Nikolay; Maestá, Sirlei Aparecida [UNESP]; Ávila, Fernando Antônio de [UNESP]; McIntosh, Douglas (Wageningen Academic Publishers, 2015)
Shiga toxin-producing Escherichia coli (STEC) are zoonotic, foodborne pathogens of humans. Ruminants, including sheep, are the primary reservoirs of STEC and there is a need to develop intervention strategies to reduce the entry of STEC into the food chain. The initiation of the majority of bacterial, enteric infections involves colonisation of the gut mucosal surface by the pathogen. However, probiotic bacteria can serve to decrease the severity of infection via a number of mechanisms including competition for receptors and nutrients, and/or the synthesis of organic acids and bacteriocins that create an environment unfavourable for pathogen development. The aim of the current study was to determine whether the administration of a probiotic mixture to sheep experimentally infected with a non-O157 STEC strain, carrying stx1, stx2 and eae genes, was able to decrease faecal shedding of the pathogen. The probiotic mixture contained Lactobacillus acidophilus, Lactobacillus helveticus, Lactobacillus bulgaricus, Lactobacillus lactis, Streptococcus thermophilus and Enterococcus faecium. The numbers of non-O157 STEC in faecal samples collected from sheep receiving daily doses of the probiotic mixture were significantly lower at the 3rd, 5th and 6th week post-inoculation when compared to the levels recorded in untreated animals. It was concluded that administration of the probiotic mixture reduced faecal shedding of non-O157 STEC in sheep, and holds potential as a pre-harvest intervention method to reduce transmission to humans.
Keywords: Enterococcus faecium; Escherichia coli; Lactobacillus; Streptococcus thermophiles; non-O157; STEC